Relationships between registrars' competency, work climate and work efficiency at land offices in Malaysia - Mohamed Ibramsah, Mazrina (2012)
Globalization challenge has force public sector as well as private sector to improve their service delivery through human resources ability and capabilities.Efficient public service workforce will help to ensure business success, continuous economic development and national competitiveness. This study focuses on an empirical research on work efficiency performance among registrars at Land offices in Malaysia. The aim of this study is to determine the level of competency, work climate and work efficiency among registrars. The study also examines the relationship between registrars’competency, work climate and work efficiency and what are the predictors that explain the variance in dependent variable. Altogether, this study has twelve independent variables and one dependent variable. The independent variables are grouped into two dimensions, which are competency and work climate. The competency dimensions are: managerial leadership skill, communication skill, registrar specific knowledge, work experience at land office, self-concept and motive. Another dimension is work climate: structure, standard, responsibility, recognition, support and commitment. The dependent variable is level of work efficiency. The primary data were collected through self-administered questionnaires distributed among 208 registrars from 105 land offices at National Land Administration Conference 2011. The secondary data for work efficiency were then collected and calculated from Land Registration Computerize System (SPTB) based on the completed questionnaires received. The findings revealed that based on the mean values the respondents perceived highly in competencies: managerial leadership skill, communication skill,registrar’s specific knowledge, self–concept, motives, and work climate: structure, standard, responsibility, and recognition, support and commitment as well as work efficiency. It also indicated that both registrar competency and work climate was positively related with their work efficiency. It also resulted that all the hypotheses were supported. In addition, the results showed that the competency variables: managerial leadership skill, registrar specific knowledge, motive and work climate variables: responsibility, recognition, and commitment were found to be positively significant in explaining work efficiency. However, communication skill, work experiences, self-concept, structure, standard and support did not significantly predict the level of work efficiency. Therefore, it can be concluded that the level of competency, work climate are high and level of work efficiency are moderate among registrars at land offices in Malaysia. There are also positive and strong relationship between competency, work climate and work efficiency among registrars at land offices in Malaysia. This study suggests that the Ministry of Natural Resources and Environment should pay attention and effort to create positive work climate and keep improving registrar’s knowledge, technical skill, soft skill and achievement motivation level in order to further enhance registrar work efficiency.